INTRODUCTION TO AFRICA YAM BEAN (SPHENOSTYLIS STENOCARPA (HOCHST. EX A. RICH.) HARMS) - OLUWAYOMI AGBOWURO, GBENGA (Innovare Journal of Agricultural Sciences, 2021)
Food security and malnutrition are great concerns in developing and under-developed nations. Climate change, political unrest, and all sorts of crises within these nations and their neighboring nations have contributed greatly to the issue of food insecurity, malnutrition, and hunger. Many food plants that have the potential to combat the challenges of food insecurities and malnutrition in the face of climate change have been neglected, under-utilized and some of the crops are on their way to extinction. African yam bean (AYB) is one of the numerous crops with great potential in overcoming the problems associated with food and nutritional insecurities. AYB under-utilization, poor acceptance, and neglect by the farmers and consumers may be a result of poor awareness about its nutritional and health benefits, poor agronomy practices adopted by the farmers, and other production limiting factors such as low yield and long maturity period. Information that can guide the farmers and consumers for the commercial production and processing of AYB is not readily available. This review aims to summarize and made available information on AYB for the farmers and the consumers for it to be commercialized and for the researchers to see reasons and areas to make improvements on the crop.